Analysis of Bankers' Perceptions About Smart Technology, Artificial Intelligence, Robotics, and Algorithms (STARA) - Kurniawan, Dediek Tri; Kusnayain, Yesiana Ihda; Syaiful (Jurnal Aplikasi Manajemen, 2026)
The rapid advancement of world technology has had a significant impact on all sectors of work, one of which is banking. From the employee side, technological advances have the potential to take over their jobs in the future. This study aims to investigate the relationship between STARA (Smart Technology, Artificial Intelligence, Robotics, and Algorithms) awareness and job insecurity, as well as job outcomes (job satisfaction and organizational commitment) among banking employees. Data were collected from 171 employees of a state-owned bank in Pekanbaru City, Indonesia. The findings prove the influence of STARA awareness on job insecurity and organizational commitment. Interestingly, STARA awareness in this study was found to affect job satisfaction positively. STARA awareness has been found to increase employees' job satisfaction. However, this study did not confirm a significant effect of STARA awareness on organizational commitment, nor did it support the moderating role of expectation retraining in the relationship between STARA awareness and job insecurity. These results indicate that new technologies are not only considered a threat to job reduction. The implementation of new technologies in banking has introduced roles such as AI data scientists, AI analysts, and robotic process automation specialists. Therefore, companies need to design strategies to prepare employees for changes in the business environment, including mastery of new fields or technologies.